Peran Laju Endap Darah dalam Evaluasi Penyakit Inflamasi Kronik - Faraztya Purnama Sari; Putu Ristyaning Ayu Sangging; Risti Graharti (CV. Jasa Sukses Abadi, 2026)
Chronic inflammation is a persistent immune response resulting from continuous inflammatory stimuli, such as chronic infections, autoimmune diseases, and metabolic disorders, and plays a significant role in the pathogenesis of various chronic diseases. Continuous evaluation of inflammatory activity requires laboratory parameters that are easily accessible and capable of reflecting long-term inflammatory processes. The erythrocyte sedimentation rate (ESR) is a non-specific hematological test that remains widely used in clinical practice to assess systemic inflammation. Elevated ESR values occur as a result of changes in acute-phase proteins, particularly fibrinogen and immunoglobulins, which promote erythrocyte aggregation and accelerate the sedimentation process. This review article aims to discuss the role of ESR in the evaluation of chronic inflammatory diseases, including the mechanisms underlying ESR elevation, its advantages, limitations, and comparison with other inflammatory biomarkers. ESR has advantages in representing stable chronic inflammation, its simplicity, and relatively low cost; however, it also has limitations, including low specificity and a slow response to changes in inflammatory activity. Therefore, ESR should be interpreted comprehensively in conjunction with clinical evaluation and other inflammatory biomarkers to support optimal management of chronic inflammatory diseases.